Pesan Selflove Dalam Lagu “Tutur Batin” Karya Yura Yunita - Lisiana Dewi; Mutiara Gustiyarni (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2023)
ABSTRACT This study aims to discuss Yura Yunita's song, "Ujar Batin". This song has a meaning about a woman's self-acceptance. Given the many problems experienced by women regarding anxiety, depression, fear, beauty standards, toxic femininity. This research includes qualitative descriptive research based on the constructivism paradigm. The method used in this study was Roland Barthes' semiotic analysis. This research shows the existence of selflove messages conveyed by songwriters, especially regarding the process of self-acceptance which is very complex according to what many women experience.